In memory of Oleh Maksymovych Rusakov (13.10.1936—13.12.2023) - Старостенко, В.І.; Кутас, Р.І.; Михайлова, Н.П.; Пашкевич, І.К.; Карабович, С.В.; Коболев, В.П.; Соловйов, В.Д.; Легостаєва, О.В.; Щипцов, О.А. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2024)
In memory of Oleh Maksymovych Rusakov (13.10.1936—13.12.2023)